Investigating Indonesian conversation; Approach and rationale - Ewing, Michael C. (Wacana, Journal of the Humanities of Indonesia, 2018)
Colloquial Indonesian has often been described in terms of its differences from standard Indonesian, but with such an approach, aspects of informal language usage will go unexplored. This article proposes using the theoretical approach of Interactional Linguistics to more adequately describe the dynamic nature of Indonesian as actually used by its speakers. Interactional Linguistics emphasizes usage-based analysis of natural language data, especially conversation, in order to understand relationships between social actions and language structure. This article gives an overview of Interactional Linguistics, illustrated by two short English examples taken form the literature. It then presents an analysis of two aspects of Indonesian grammar – subject expression and clause structure – using an Interactional Linguistics approach to examine conversational data. By presenting an alternative analysis of two aspects of Indonesian grammar, this article aims to promote the use of Interactional Linguistics for examining the grammar of Indonesian and other languages of Indonesia.